2024
DOI: 10.3390/jmse12020207
|View full text |Cite
|
Sign up to set email alerts
|

XFEM-Based Study of Fatigue Crack Propagation in Rocket Deflector Troughs under Coupled High-Temperature and Impact Conditions

Zhixin Xiong,
Chengyuan Zhu,
Yue Yang
et al.

Abstract: This research investigated fatigue crack propagation on the lower surface of rocket deflector troughs in offshore rocket launch platforms. Initially, a numerical model of an offshore rocket launch platform was established using ABAQUS based on the Extended Finite Element Method (XFEM). Subsequently, two variable parameters—the initial crack length and initial tilt angle—were introduced. This research systematically analysed the impact of these parameters on the fatigue crack propagation patterns in both the ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Pua et al [27] simulated the impact of hydrogen combustion following a hydrogen leak accident on offshore launch platforms and the preventive effect of protective walls, demonstrating that wall design can effectively protect rockets from combustion impacts. Xiong et al [28] studied the influence of initial crack length and initial tilt angle on fatigue crack propagation on the lower surface of rocket deflector channels of offshore rocket launch platforms using the Extended Finite Element Method (XFEM). Yu et al [29] indicated that launch vehicle lateral eccentricity during launch can induce significant rolling motion in the platform.…”
Section: Introductionmentioning
confidence: 99%
“…Pua et al [27] simulated the impact of hydrogen combustion following a hydrogen leak accident on offshore launch platforms and the preventive effect of protective walls, demonstrating that wall design can effectively protect rockets from combustion impacts. Xiong et al [28] studied the influence of initial crack length and initial tilt angle on fatigue crack propagation on the lower surface of rocket deflector channels of offshore rocket launch platforms using the Extended Finite Element Method (XFEM). Yu et al [29] indicated that launch vehicle lateral eccentricity during launch can induce significant rolling motion in the platform.…”
Section: Introductionmentioning
confidence: 99%